Training young female entrepreneurs on a national-scale: the Greek 'Genesis' Project case study - Zarkada, Anna K.; Kapareliotis, Ilias (My University, 2021)
This paper presents a model of training for young females in metropolitan as well as semi-urban and rural areas addressing the barriers and skill and competencies needs of a generally disadvantaged social group. The model formed the basis of a large scale intervention implemented through a partnership between the largest in terms of research output and student numbers Greek universities and government. The development, deployment and evaluation process are detailed and conclusions and recommendations on how this project can serve as a blueprint for other countries wishing to address the problem of female employment and economic development through entrepreneurship with an emphasis on new technologies.
Keywords: Gender issues; Education and training; Entrepreneurship